“Look! This one looks like a mountain with a little bit of sea” - Social Dimensions of food: a look inside childhood - Lessa, Juliana (Aprender, 2024)
This work is the result of doctoral-level research that investigated feeding moments in the routine of early childhood education and sought to understand the ways in which children appropriate this space-time, directing a look at their actions, mediated by eating practices. The analyses are based on data generated in field research, carried out in the cafeteria of a public early childhood education unit, located in the city of Florianópolis, SC, Brazil. Participant observation and the detailed description of the relationships investigated, methodological procedures of ethnography, were the main instruments for generating research data. Practicing listening to the senses that circulate among children when they are at the table highlights the importance that the social and affective context of eating practices has for them. The research data are discussed in two parts: first, it addresses the ethical and methodological challenges of conducting research with children and, secondly, some episodes of the field research are presented, analysing them as indicators that inform early childhood education about the interactive and symbolic-affective aspects that affect children's eating practices. And, in general, they inform us about how their humanization process occurs, as a subject that is constituted in and by culture.
Keywords: early childhood education; canteen; food; eating practices; childhood cultures